2018
DOI: 10.5582/bst.2018.01015
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration characteristics and influencing factors of retroperitoneal liposarcoma: Novel evidence for extended surgery and a tumor grading system

Abstract: This study sought to evaluate the infiltration tendency of retroperitoneal liposarcoma (RPLS) from a new pathological angle by exploring the infiltration characteristics, which could provide helpful information to facilitate surgical decision-making and prognosis prediction. Concurrently, we aim to identify significant indicators of infiltration. A total of 61 consecutive patients with RPLS at our institution were retrospectively analyzed. All patients received extended surgery. The tumor infiltration characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…R0 resection of a large retroperitoneal liposarcoma was associated with a 85.7% five-year survival compared to 33.3% following R1 resection (39). Wang et al suggested that extended resection that includes adjacent organs is beneficial in order to achieve radical treatment (40). Bradley et al reported that over 50% of successful complete excisions also included adjacent organs (17).…”
Section: Discussionmentioning
confidence: 99%
“…R0 resection of a large retroperitoneal liposarcoma was associated with a 85.7% five-year survival compared to 33.3% following R1 resection (39). Wang et al suggested that extended resection that includes adjacent organs is beneficial in order to achieve radical treatment (40). Bradley et al reported that over 50% of successful complete excisions also included adjacent organs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Second, in this study, the decision to perform PD during RPS resection was based on the preoperative imaging features, intraoperative exploration, and our experience. Our previous report showed that in a group of 26 retroperitoneal liposarcoma patients who underwent pancreatectomy at our institute, 9 patients (34.6%) were found to have tumor infiltration of the pancreatic parenchyma and 6 (23.1%) showed tumor infiltration in the peripancreatic fatty tissue fat tissue (21). Such results clearly show that it may be necessary to consider performing pancreatic resection for the tumor adjacent to the pancreas, in particular, when the tumor is of great size.…”
Section: Discussionmentioning
confidence: 61%
“…Surgical procedures of RPS are challenging. No matter curative-intent surgery or palliative-intent surgery frequently requires a complex, multivisceral resection (27). In the present study, all patients of RPS with PS underwent MVR, referring to multiple specialties including gastrointestinal surgery, hepatopancreatobiliary surgery, urinary surgery, and vascular surgery, etc.…”
Section: Discussionmentioning
confidence: 89%